H19 Induces Abdominal Aortic Aneurysm Development and Progression. Issue 15 (9th October 2018) - Li, Daniel Y.; Busch, Albert; Jin, Hong; Chernogubova, Ekaterina; Pelisek, Jaroslav; Karlsson, Joakim; Sennblad, Bengt; Liu, Shengliang; Lao, Shen; Hofmann, Patrick; Bäcklund, Alexandra; Eken, Suzanne M.; et al.
Abstract : Background: Long noncoding RNAs have emerged as critical molecular regulators in various biological processes and diseases. Here we sought to identify and functionally characterize long noncoding RNAs as potential mediators in abdominal aortic aneurysm development. Methods: We profiled RNA transcript expression in 2 murine abdominal aortic aneurysm models, Angiotensin II (ANGII) infusion in apolipoprotein E–deficient ( ApoE −/− ) mice (n=8) and porcine pancreatic elastase instillation in C57BL/6 wild-type mice (n=12). The long noncoding RNA H19 was identified as 1 of the most highly upregulated transcripts in both mouse aneurysm models compared with sham-operated controls. This was confirmed by quantitative reverse transcription–polymerase chain reaction and in situ hybridization. Results: Experimental knock-down of H19, utilizing site-specific antisense oligonucleotides (LNA-GapmeRs) in vivo, significantly limited aneurysm growth in both models. Upregulated H19 correlated with smooth muscle cell (SMC) content and SMC apoptosis in progressing aneurysms. Importantly, a similar pattern could be observed in human abdominal aortic aneurysm tissue samples, and in a novel preclinical LDLR −/− (low-density lipoprotein receptor) Yucatan mini-pig aneurysm model. In vitro knock-down of H19 markedly decreased apoptotic rates of cultured human aortic SMCs, whereas overexpression of H19 had the opposite effect. Notably, H19-dependent apoptosis mechanisms in SMCs appeared to be independent of miR-675, which is embedded in the first exon of the H19 gene. A customized transcription factor array identified hypoxia-inducible factor 1α as the main downstream effector. Increased SMC apoptosis was associated with cytoplasmic interaction between H19 and hypoxia-inducible factor 1α and sequential p53 stabilization. Additionally, H19 induced transcription of hypoxia-inducible factor 1α via recruiting the transcription factor specificity protein 1 to the promoter region. Conclusions: The long noncoding RNA H19 is a novel regulator of SMC survival in abdominal aortic aneurysm development and progression. Inhibition of H19 expression might serve as a novel molecular therapeutic target for aortic aneurysm disease. Abstract : Supplemental Digital Content is available in the text.